KEPALA SEKOLAH SEBAGAI MOTIVATOR: Upaya Meningkatkan Kinerja Guru di Mts N 01 Kepahiang - Sri Hartinah; Wiwin Arbaini; Arsil Arsil; Hamengkubuwono Hamengkubuwono (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2020)
This study aimed to find a portrayal of the principal’s efforts to improve teachers’ performance at MTs 01 of Kepahiang. This study used a qualitative approach. The main sources were the principal and teachers. To obtain such a portrayal, the data were collected through observation, interviews, and documentation. After the data were collected, they were then reduced, presented, and discussed so as to find the desired conclusion. The conclusion of this study was that the principal as a manager must make efforts to do many ways in order that teachers could improve their performance so that the learning processes became more qualified. One of the ways was by giving motivation to teachers. Constraints faced by the principal in motivating teacher performance stemmed from the teachers themselves whose intrinsic motivation was still low and had implications for their abilities. There were still found some teachers who were less able to describe lesson plans and syllabus correctly.  These teachers only carried out teaching tasks without being supported by careful planning.Keywords: Principal, Teacher Performance, Motivator